The Subtitling Strategies Adopted to Render the Four-Letter Words 'Fuck, Shit' and Their Variants in the French Version of 'Orange Is the New Black: 'A Corpus-Based Study - Eponine Moreau (Anglo Saxonica)
This paper aims to investigate the translation strategies used to render swear words from English into French subtitles in Netflix Original Series. More specifically, we present the methodology applied to describe the translation strategies used to render 200 instances of the swear word fuck and 138 instances of the swear word shit in the first season of Orange Is the New Black (OITNB). All 338 instances were classified into six strategies, partly drawing on existing typologies of subtitling strategies. While the omission and standardization strategies have been borrowed from existing typologies, the definitions of the euphemism and maintenance strategies have been adapted. The textual analyses also allowed for the identification of two new translation strategies. Although less frequent in the corpus, these strategies, called direct compensation and pragmatic softening, are thought to better reflect French idiosyncrasies and complement existing typologies.